A Review of Atmospheric Aerosols in Antarctica: From Characterization to Data Processing - Anzano, Jesús; Abás, Elisa; Marina Montes, César; Del Valle, Javier; Galán Madruga, David; Laguna, Mariano; Cabredo, Susana; Pérez Arribas, Luis Vicente; Cáceres, Jorge Omar; Anwar, Jamil (Atmosphere, 2022)
One of the major problems of the present era is air pollution, not only for its impact on climate change but also for the diseases provoked by this scourge. Among the most concerning air pollutants is particulate matter, since it can travel long distances and affect the entire globe. Antarctica is extremely sensitive to climate change and essential for regulating temperature and permitting life on Earth. Therefore, air quality studies in this region are extremely important. The aim of this review is to present the work conducted on the identification and detection of aerosols and particulate matter in the Antarctic region in the last 20 years. These studies revealed a large number of organic and inorganic species. Organochlorine pesticides or polychlorinated biphenyls represent almost 50% of the organic fraction detected in Antarctica. Furthermore, heavy metals such as Hg and Pb were also found in the region related to anthropogenic activities. To summarize, this work detailed different analytical techniques and data processing to help characterize Antarctic aerosols and their potential sources. Universidad de Zaragoza Departamento de Ciencia, Universidad y Sociedad del Conocimiento del Gobierno de Aragón Ministerio de Ciencia, Innovación y Universidades (España) Gobierno de España Depto. de Química Analítica Fac. de Ciencias Químicas TRUE pub